Psychological Well-Being Mediates the Effect of Permissive Parenting on Online Game Addiction in Children (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The increasing addiction to online games among children has become a concerning phenomenon, especially when linked to permissive parenting, which tends to provide excessive freedom without clear boundaries. This study aims to analyze the relationship between permissive parenting and online game addiction, with psychological well-being as a mediating variable. The method used is a qualitative approach with a Systematic Literature Review (SLR), where scientific articles from indexed databases such as Scopus, WoS, and Sinta in the last ten years were systematically reviewed. The results show that permissive parenting has a positive correlation with online game addiction, where children given excessive freedom tend to lack self-regulation and impulse control. However, psychological well-being acts as a mediating factor that can reduce the negative impact of permissive parenting on online game addiction. Children with good psychological well-being have lower levels of addiction compared to those experiencing emotional imbalance. The implications of this study highlight the importance of more balanced parenting styles and strategies to enhance children's psychological well-being in preventing online game addiction.